EGFR Immunohistochemical Expression in Head and Neck Squamous Cell Carcinoma and its Prognostic Significance - Fameena Rahman Shaik; Vijaya Lakshmi Muram Reddy; Pratima Jonnadula; Durga Kharidehal; Syam Sundara Rao Byna; Bhavana Grandhi (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Head and neck Squamous cell carcinoma (HNSCC) is a highly rapidly spreading invasive malignant tumour of the epithelium and in the entire world, it is the sixth most common malignant neoplasm. EGFR protein is crucial for several processes that impact tumor genesis, growth, differentiation, suppression of apoptosis and metastatic development. Increased expression of EGFR is linked to poor clinical outcomes and resistance to radiation therapy. Aim: Evaluation of expression of EGFR is done in HNSCC and it is correlated with various parameters like histological grade, staining intensity, percentage of tumor cells stained and its prognostic signi𿿿cance is determined. Materials and methods: Total number of 80 cases were studied and statistically p value is determined. Results: Females holds the majority of 51cases (63.75%) and males were 29 cases (36.25%). Age group 41 to 50 years has highest occurrence which is followed by 51 to 60 years. 63.75% of patients have positive smoking history. 71.25% have history of tobacco use. Most common site of tumor is oral cavity (95%). Majority of the cases were conventional Squamous Cell Carcinoma (95%) and verrucous carcinoma comprising (5%) cases. Most of the patients had grade I tumors (53.75%). 51.25% of cases have strong intensity in staining. Greater than 50% of cells are stained by EGFR in 56 cases and p value is statistically signi𿿿cant. Conclusion: High EGFR expression is a helpful diagnostic and prognostic immunohistochemical marker especially in advanced cancers. EGFR targeted therapy along with radiotherapy, chemotherapy can be used for locally advanced, metastatic and recurrent Head and Neck squamous cell carcinomas.